Life-cycle assessment of greenhouse gas and air emissions of electric vehicles: A comparison between China and the U.S. (May 2015) - Huo, Hong; Cai, Hao; Zhang, Qiang; Liu, Fei; He, Kebin
Abstract: We evaluated the fuel-cycle emissions of greenhouse gases (GHGs) and air pollutants (NOx, SO2, PM10, and PM2.5 ) of electric vehicles (EVs) in China and the United States (U.S.), two of the largest potential markets for EVs in the world. Six of the most economically developed and populated regions in China and the U.S. were selected. The results showed that EV fuel-cycle emissions depend substantially on the carbon intensity and cleanness of the electricity mix, and vary significantly across the regions studied. In those regions with a low share of coal-based electricity ( e.g ., California), EVs can reduce GHG and air pollutant emissions (except for PM) significantly compared with conventional vehicles. However, in the Chinese regions and selected U.S. Midwestern states where coal dominates in the generation mix, EVs can reduce GHG emissions but increase the total and urban emissions of air pollutants. In 2025, EVs will offer greater reductions in GHG and air pollutant emissions because emissions from power plants will be better controlled; EVs in the Chinese regions examined, however, may still increase SO2 and PM emissions. Reductions of 60–85% in GHGs and air pollutants could be achieved were EVs charged with 80% renewable electricity or the electricity generated from the best available technologies of coal-fired power plants, which are futuristic power generation scenarios. Graphical abstract: Highlights: Electric Vehicles (EVs) are a promising low-carbon solution to save oil worldwide. We analyzed the fuel-cycle emissions of EVs in 6 key regions of China and the U.S. EVs can reduce emissions in US California and the northeast states significantly. EVs may raise pollutant emissions in China's 3 regions and the US Midwest states. EVs will offer better environmental benefit as power plants are cleaner in future.